Not in Employment, Education, or Training around the World - Mark Levels; Christian Brzinsky-Fay; Craig Holmes; Janine Jongbloed; Hirofumi Taki (The Dynamics of Marginalized Youth, 2022)
During the economic crises in the years following 2008, policymakers of various governments regularly hit the alarm bells about the dire situation of marginalized youth in various European countries. Early-career inactivity turns Not in Education, Employment, or Training (NEETs) into the most likely candidates for long-term socioeconomic marginalization, criminal careers, and grave mental and physical health problems. Japanese NEET who have completely retreated from society, are from different social backgrounds and face different circumstances from German immigrant children who have trouble finding a job, who in turn differ from Dutch low-ability adolescents who fail to graduate from vocational education. Since the 1990s, various alternative concepts emerged in labour market research as well as among policymakers.
Keywords: 330